SHARI'A CONTEMPLATION IN THE WORLD OF SUFISM: SYNERGIZING ACPECTS OF HAQIQA AND SHARIA IN THE SUFISTIC DIMENSION - Amir Maliki Abitolkha (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2021)
This study aims to examine and analyze the concept of Shari’a contemplation in Sufism. It will show the importance of the synergy between Shari’a and Haqiqa dimensions in Sufism. This article is a literature-based study in which the data were collected from various literature, documentation, and other related sources. This study revealed that the concept of Shari’a contemplation in Sufism is a method of spiritual journey wherein someone practicing amaliah, teachings, and Sufistic life does not leave the commands of the Shari’a. The aspect of the Shari’a must be mature and still preserved with his intense closeness to Allah SWT. Contemplation of Shari›a as one of the spiritual practices emphasizes the importance of meditation and emptying the mind from everything except Allah SWT. Thus, a Salik is still obliged to carry out the Shari›a responsibilities and other obligations as a servant of Allah. In other words, contemplation is not limited to meditation physically but also inwardly, in the form of emptying everything except Allah and transforming ethical and aesthetic values into the practice of contemplation.